Does static and dynamic relationship between economic growth and energy consumption exist in OECD countries? - Bassem Kahouli (Energy Reports, 2019)
The main purpose of this paper is to investigate the relationship between economic growth (EG) and energy consumption (EC) for the 34 OECD (Organisation for Economic Co-operation and Development) countries over the period 1990-2015.Analyze the static and especially dynamic sense of relation among EG and EC in OECD always stay interesting. Using three models to examine growth-energy nexus, energy-growth nexus and the two-way linkages between them, this work consolidated the empirical insights in this research axis. Empirical results support an feedback effect between EG and EC. This results have provided key suggestions and recommendations which have important energy and economic policies implications for OECD policymakers. This ensures sustainable economic development and serve as a motivation to search alternative energy sources to meet the burgeoning energy demand in this countries.
Keywords: O40; Q43; C23; C36; 330; EC; EG; GMM; OECD countries